Review: Interaksi Antara Obat Konvensional dan Herbal untuk Diabetes Mellitus - Izzah Al Mukminah; Raden Bayu Indradi (Ikatan Senat Mahasiswa Farmasi Seluruh Indonesia, 2021)
Introduction: The prevalence of Diabetes Mellitus (DM) in Indonesia is high and has even fluctuated from 422 million to 463 million in 5 years. In the management of DM, one of which is pharmacological therapy using antihyperglycemic drugs (AHD). Currently, besides AHD, people also use herbs to treat DM. While active herbal compounds that have been shown to contribute to DM treatment are diverse and multicomponent, not all of these components are known to have therapeutic effects. Thus, the aim of this literature review is to determine the interactions that might occur between conventional and herbal drugs for DM. Method: A literature search was conducted in May 2020. The sites used were Google Scholar, Elsevier and NCBI. The keywords used to find the journal sources were